Recognition of purified beta 1,3/1,6 glucan and molecular signalling in the intestine of Atlantic salmon - Kiron, Viswanath; Kulkarni, Amod; Dahle, Dalia; Vasanth, Ghana Kalerammana; Lokesh, Jep; Elvebo, Odd (Developmental & Comparative Immunology, 2016)
Author's accepted version (post-print).